Exchange rate pass-through to import prices in the euro area - José Manuel Campa; Linda S. Goldberg; José M. González-Mínguez (Federal Reserve Bank of New York, 2005)
This paper presents an empirical analysis of transmission rates from exchange rate movements to import prices, across countries and product categories, in the euro area over the last fifteen years. Our results show that the transmission of exchange rate changes to import prices in the short run is high, although incomplete, and that it differs across industries and countries; in the long run, exchange rate pass-through is higher and close to 1. We do not find compelling evidence that the introduction of the euro caused a structural change in exchange rate pass-through. Although some estimated point elasticities have declined, structural breaks in exchange rate pass-through into import prices are evident only in a limited sample of manufacturing industries. And since the euro was introduced, industries producing differentiated goods have been more likely to experience reduced rates of exchange rate pass-through to import prices. Exchange rate changes continue to lead to large changes in import prices across euro-area countries.
Keywords: F3; F4; 330; currency; invoicing; pass-through; exchange rate; producer currency pricing; local currency pricing; Exchange Rate Pass-Through; Außenhandelspreis; Euro; EU-Staaten